PENGARUH PENERAPAN MEDIA LIRIK LAGU TERHADAP KETERAMPILAN MENULIS PUISI ANAK SISWA SEKOLAH DASAR - Susanti, Susi; Halidjah, Siti; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThe purpose of this research was to know the effect of media song lyrics on poetry writing skill in learning student fifth grade Elementary School in Kecamatan Badau. The experiment reseach method was used in this research. The form of the experiment research used was one group pretest postest design. Sample in this research weer students fourth grade which consisted of 35. Instrument gatherer data of student learning the test results obtained using measurement technique. Instrument gatherer data of student learning the test results obtained from pre-test and post-test. The result of data analysis showed that mean score of student?s post-test was 72,85. Based on t-test analysis, thitung of  (17,54) and ttabel (1,697). Which means, thitung (17,54) >ttabel (1,697), then Ha accepted. The result of effect size was 0,86 which mean high criteria on ES>0,7. So, it can be concluded there was a significant effect of using media song lyrics on poetry writing skill in learning student fifth grade Elementary School in Kecamatan Badau. Keywords:Effect, Media song lyrics, Poetry writing skill.